(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
The Right of Consultation (DC), as a participation mechanism for indigenous peoples affected by natural resource exploitation projects, has been outlined in terms of its content, scope and purpose by the Inter-American Human Rights System (IAHRS). The IAHRS is integrated by the American Convention on Human Rights (ACHR), the Inter-American Court of Human Rights and the Inter-American Commission on Human Rights. The main means by which the IAHRS has been issued on the DC are the judgments of the Inter-American Court of Human Rights (I / A Court HR) in the Saramaka v. State of Surinam and the Kichwa of Sarayaku v. Ecuador cases. This paper intends to analyze the pronouncements of the Inter-American Court on the right of consultation of indigenous communities in the light of legal trialism.